A-61 Predictors of Subjective and Objective Everyday Functioning in Middle-Aged and Older Adults with HIV. (30th August 2021) - Jacob, Alexandra E; Crowe, Michael; Fazeli, Pariya L; Vance, David E
Abstract: Objective: Older adults with HIV are at increased risk for difficulties with instrumental activities of daily living (IADLs). Awareness of their functional capacity has emerged as an important area for research, but it is not well studied in PWH. The purpose of this study is: (1) to identify factors associated with subjective and objective IADL difficulty in PWH and (2) to identify factors associated with under- or over-reporting of IADL difficulties. Methods: This cross-sectional study included 261 adults with HIV. Participants completed a neuropsychological battery, self-report and performance-based measures of IADLs. Self-report measures included the Patient's Assessment of Own Functioning Inventory (PAOFI) and the Lawton and Brody IADL Questionnaire. The Timed Instrumental Activities of Daily Living (TIADL) task was used as an objective measure. Hierarchical multiple regressions were performed to identify factors associated with subjective and objective assessment of everyday functioning as well as factors associated with discrepancy between self-report and actual performance of IADLS. Results: On the PAOFI, higher depression (p = 0.001), lower conscientiousness (p > 0.001), and better processing speed (p = 0.017) predicted worse functioning. On the Lawton and Brody, higher depression (p = 0.049) predicted of worse functioning. On the TIADL, older age (p = 0.1), lower WRAT-4 score (p > 0.001), worse processing speed (p > 0.001), and worse motor function (p = 0.1) were associated with worse performance. Processing speed predicted discrepancy between subjective and objective performance of IADLs (p = 0.1). Conclusions: Several demographic, cognitive, and personality variables are associated with worse subjective and objective everyday functioning, as well as an individual's ability to accurately self-appraise their functional capacity.